PARTISIPASI KELOMPOK TANI TERHADAP DINAMIKA KELOMPOK TANI DI DESA ONGKAW DUA KECAMATAN SINON SAYANG KABUPATEN MINAHASA SELATAN - Asri Indri Roring; Celcius ., Talumingan; Agnes E. Loho (Sam Ratulangi University, 2018)
This study aims to determine the participation of farmer groups against the dynamics of farmer groups in the Village Ongkaw Dua Sinon Sayang District South Minahasa District. This research was carried out in Ongkaw Dua Village, Sinon Sayang District, South Minahasa District for 3 months starting from February 2017 until April 2017 starting from preparation, taking data to preparing research report. Data collection methods in this study using primary data and secondary data. Primary data were obtained directly from the source through surveys and interviews using questionnaires to the Four Farmers Group of the Ark, Sinar Baru, Bersehati, Blessing each five group members consisting of chairman, secretary, treasurer, and two members of the farmer group, while secondary data was obtained from institutions related to the research of the village government Ongkaw Dua Based on the results of descriptive analysis it can be seen that the number of farmer group participation index to the dynamics of farmers group is very good with the score obtained is 3600.